Prevalence of in vitro susceptibility to carbapenems among clinical isolates of the Bacteroides fragilis group from a Colombian tertiary hospital. Issue 1 (March 2014) - Salazar, C.L.; Cataño, J.C.; Molina, D.; Sierra, P.; Correa, M.
Abstract: Clinical isolates of the Bacteroides fragilis group ( n  = 29) were collected from patients attending a tertiary care hospital in Medellin, Colombia, during 2012 and were tested for susceptibility to four carbapenems using the Clinical and Laboratory Standards Institute (CLSI) Etest method. Overall rates of percent susceptibility were as follows: meropenem, 93.1%; imipenem, 100%; ertapenem, 96.6%; and doripenem, 93.1%. This is the first study to show rates of resistance of Bacteroides spp. to carbapenems in Colombia among a species formerly thought to be fully susceptible to this type of antimicrobial.